Penalaran Abduktif Siswa SMP dalam Menyelesaikan Masalah Matematika Ditinjau dari Gaya Kognitif Field Dependent dan Field Independent - Meliani Dwi Pertiwi; Ali Shodikin (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2026)
Abductive reasoning is the process of formulating conjectures to explain surprising observations. Although these conjectures are not necessarily true, this type of reasoning is highly helpful in problem-solving for determining the best solution strategy. This study aims to investigate the differences in abductive reasoning across different cognitive styles. This research method uses a qualitative descriptive approach. The participants in this study were 32 students. Two of them were then selected for in-depth interviews representing types of abductive reasoning. Data collection and analysis were carried out on students' work results and semi-structured interviews. Polya's problem-solving theory was used to analyze students' thinking processes using abductive reasoning. The analysis was conducted on all problem-solving steps, namely understanding the problem, devising a plan, carrying out the plan, and looking back. Students with a field independent cognitive style were able to recognize and understand the problem quickly and directly determine the appropriate formula. In contrast, students with a field dependent cognitive style tended to understand the problem globally, requiring more time to complete the questions.